Does household air pollution from cooking fires affect infant neurodevelopment? Developing methods in the NACER pilot study in rural Guatemala - Dr. Lisa M Thompson, PhD; Guinevere Valencia-Moscoso, MS; Renée Asteria Peñaloza, MPH; Anaité Díaz Artiga, MPH; Eduardo Canúz, BS; Kirk R Smith, PhD; S Katharine Hammond, PhD (Elsevier, 2014)
Background: Worldwide, 3 billion people are exposed to household air pollution from cooking fires. One of the top two risk factors among neonates, household air pollution greatly affects neonatal morbidity and mortality. In low-resource countries, neurodevelopmental impairments are often not identified during the neonatal period, leading to permanent disability. No published studies have examined the effect of household air pollution exposures on neurodevelopmental impairments in infants. The NACER study in rural Guatemala aims to measure personal exposures to household air pollution during pregnancy and infancy and to train birth attendants to collect standardised measures of infant neurodevelopment. Methods: Guatemalan indigenous women from rural communities were recruited from a health centre at less than 20 weeks' gestation and received prenatal health exams at less than 20 weeks, 24-28 weeks, and 32-36 weeks. The study was conducted between January, 2012, and December, 2013. Home visits were made three times during pregnancy to monitor prenatal exposures to carbon monoxide (particulate matter; PM2·5) and polycyclic aromatic hydrocarbons. Home visits were made within 48 h of birth and at 1, 3, 6, 9, and 12 months to assess household air pollution exposures and measure infant neurodevelopment with a validated 27-item instrument (Rapid Neurodevelopmental Assessment) developed in Bangladesh for use with semi-skilled health workers and adapted in Guatemala for use with traditional birth attendants. We report on household air pollution and results from Rapid Neurodevelopmental Assessment from the prenatal and neonatal periods. Findings: 37 pregnant women were enrolled and there were 31 liveborn infants. Gestational age was confirmed by fetal ultrasound (mean 15·2 weeks, range 7-20·1). Five (11%) households used open fires for cooking, whereas 33 (89%) used deteriorated chimney stoves. Mean 15-min maximum exposure to carbon monoxide were 16·9 parts per million (ppm, SD 12·4) during the prenatal period and 13·3 ppm (SD 23·4) during the neonatal. Mean 48-h PM2·5 concentrations were 130·2 μg/m3 (SD 65·3) during pregnancy and 63·8 μg/m3 (SD 17·3) during the neonatal period. 27% of infants were low birthweight (<2500 g) and 8% were preterm (<37 weeks). Of neonates, moderate/severe neurodevelopmental impairments, as defined by the Rapid Neurodevelopmental Assessment cutoff points, were identified in eight domains: fine motor (n=4, 13%), gross motor (10, 32%), speech (5, 16%), cognition (5, 16%), behaviour (4,13%), vision (1, 3%), hearing (6, 19%), and primitive reflexes (7, 23%). Interpretation: Maternal exposures to household air pollution were higher than were neonatal exposures, but both were higher than WHO recommended guidelines. Low birthweight and moderate/severe neurodevelopmental impairment were high. Pilot data will be used to develop a future, randomised stove intervention study to measure the effect of reduced exposures to household air pollution on low birthweight, preterm delivery, and infant neurodevelopmental impairment. Funding: University of California, National Center for Advancing Translational Sciences, National Institutes of Health.